Biomass-derived porous activated carbon from anacardium occidentale shell as electrode material for supercapacitors. (20th April 2022) - Hepsiba, P.; Rajkumar, S.; Elanthamilan, E.; Wang, Sea-Fue; Princy Merlin, J.
Abstract : Anacardium occidentale shell (AOS) biowaste was chemically activated using KOH at various temperatures to produce AC. Interestingly, this study also presents a novel strategy for achieving value-added usage of cashewnut shell in the energy storage field. Abstract : The cashewnut ( Anacardium occidentale ) is extensively used worldwide as an important nutrients source. Herein, we propose a simple, low-cost approach for producing activated carbon (AC) from a biomass source. Anacardium occidentale shell (AOS) biowaste was chemically activated using KOH at various temperatures (600 °C, 700 °C, 800 °C and 900 °C) to produce AC. The surface functional groups, disordered nature and morphology of the ACs were examined by different physico-chemical tools. The FESEM analysis of AOS–PCC showed a normal flat surface without any pores, whereas AOS-6 to AOS-9 displayed a flat surface with abundant pores due to KOH impregnation and activation, which facilitated the formation of such a distinctive structure. The electrochemical studies of these carbon materials confirmed their promising characteristics for applications in supercapacitors (SCs). The electrochemical characteristics of AOS–AC samples were tested in 1 M KOH in a potential window between 0 and 1 V using different electroanalytical techniques in a three-electrode system. The as-prepared AOS-9, possessing a large specific surface area (854.31 m 2 g −1 ) displayed an outstanding electrochemical performance for SCs, with a high capacitance (393 F g −1 at 1 A g −1 ) and great cycle stability (92.6% capacitance retention even after 8000 cycles at 1 A g −1 ). The study demonstrated a promising low-cost, easily scalable manufacturing method for advanced electrode materials for SCs.